(untitled) (Boletín Semillero de Investigación en Familia, 2026)
Background: Children and adolescents living with cancer employ diverse cognitive and behavioral strategies to manage stressors. Characterizing these strategies can inform nursing interventions tailored to patients’ developmental needs and sociocultural context. Objective: To describe the frequency and perceived effectiveness of coping strategies among 8–15-year-old patients with cancer in Bogotá. Materials and Methods: We conducted a descriptive, cross-sectional study using convenience sampling at a healthcare institution in Bogotá. Coping was assessed with the Schoolagers’ Coping Strategies Inventory (SCSI). Data were managed in Excel and analyzed in R. Results: Frequently reported strategies included nail-biting, withdrawing, seeking a safe place, playing, praying, and communicating with parents. Strategies most often rated as effective were communicating with parents, hugging, relaxation,M play and other enjoyable activities, problem-solving, distraction (thinking about something else), and telling the truth. Conclusion: Coping strategies are widely used by pediatric oncology patients. Nursing care should systematically identify these patterns and incorporate developmentally appropriate, family centered approaches that reinforce effective strategies within the plan of care.